A review of sugarcane bagasse for second‐generation bioethanol and biopower production. (20th July 2016) - Bezerra, Tais Lacerda; Ragauskas, Art J.
Abstract: Sugarcane bagasse is a large‐volume agriculture residue that is generated on a ~540 million metric tons per year basis globally 1, 2 with the top‐three producing countries in Latin America being Brazil (~181 million metric ton yr −1 ), 3 Mexico (ܾ15 million metric ton yr −1 ), 4 and Colombia (ܾ7 million metric ton yr −1 ), 5 respectively. 6 Given sustainability concerns and the need to maximize the utilization of bioresources, the use of sugarcane bagasse is receiving significant attention in biorefining applications, as it is a promising resource for the conversion to biofuels and biopower. This review provides a comprehensive review of bagasse and its chemical constituents and on‐going research into its utilization as a feedstock for cellulosic ethanol and electricity generation. © 2016 Society of Chemical Industry and John Wiley & Sons, Ltd